Assessment of Functional Fibrinolysis in Cord Blood Using Modified Thromboelastography. Issue 5 (8th January 2016) - Sidlik, Rakefet; Strauss, Tzipora; Morag, Iris; Shenkman, Boris; Tamarin, Ilia; Lubetsky, Aharon; Livnat, Tami; Kenet, Gili
Abstract : Background: The fibrinolytic system in newborns is immature and probably impaired. The aim of this study was to prospectively evaluate functional fibrinolytic capacity of newborn's cord blood using a new thromboelastometry (rotational thromboelastogram, ROTEM ® ) test. Methods: Infants born at Sheba Medical Center were studied prospectively. Cord blood was obtained immediately after clumping, and ROTEM parameters were assessed applying non‐activated TEM (NATEM) assay with increasing concentration of tissue plasminogen activator (tPA, 0–200 U/ml). Baseline clotting time (CT), clot formation time (CFT), alpha angle, and maximum clot firmness (MCF) were compared among infants versus adults. Each infant's demographic information was prospectively followed up until discharge. Results: One hundred one newborns were tested. CT and CFT values were lower and alpha angles were higher among neonate's cord blood compared to adults (n = 23; P  = 0.001, 0.03, and 0.02, respectively). The addition of tPA significantly shortened CT and CFT, and reduced alpha angles and MCF in both groups. The lysis index at 30 min (LI30) and lysis onset time (LOT) decreased significantly, and fibrinolysis was more rapid in the newborns. Hematocrit and platelet counts in neonates correlated with LI30 ( P = 0.035 and 0.037, respectively) and LOT ( P  = 0.02) when higher tPA concentrations were used. ROTEM values were unrelated to the occurrence of postnatal complications. Conclusions: This first report of functional fibrinolysis in cord blood demonstrated that neonatal fibrinolysis may be augmented as compared to adult values. Further studies are required to validate this test and assess its predictive value and clinical relevance.